Sveriges avrasifiering Svenska uppfattningar om ras och rasism under efterkrigstiden - Hübinette, Tobias; Wikström, Peter (Kriterium, 2023)
The deracialization of Sweden is a research anthology that examines issues of race, racism, anti-racism and whiteness in a Swedish post-war and contemporary context. The anthology consists of 13 studies written by authors from different fields that collectively explore how the concept of race was gradually dismantled and eventually became taboo in Sweden after 1945, and how a specifically Swedish form of anti-racism instead became normative. The anthology's contributions can be seen as case studies, focusing on key persons, public debates, figures of thought, institutions, migration and marketing, based on material from archives, the daily press, interviews, social media and more. Through this empirical and methodological breadth, the anthology as a whole cross-sections Sweden's evolution from being a race science pioneer to becoming the world's most distinctly "colorblind" country. The book is edited by Tobias Hübinette and Peter Wikström, with contributions written by Martin Ericsson, Johan Samuelsson, Ludwig Schmitz, Emma Severinsson, Mattias Tydén, Mats Wickström, David Assadkhan, Karin Idevall Hagren, Catrin Lundström, Sayaka Osanami Törngren and Jeff Werner.